Liberação endoscópica do túnel cubital na neurite hansênica do nervo ulnar - Sampaio, Antônio Carlos Delgado (2022)
Ulnar nerve compression at the elbow is commonly called cubital tunnel syndrome, being the second most common compressive neuropathy of the upper limb, statistically second only to carpal tunnel syndrome. To better characterize the role of endoscopic cubital tunnel release in leprosy neuritis and determine whether there is an improvement in pain, sensitivity and strength with the use of this minimally invasive technique. A total of 44 endoscopic procedures for ulnar nerve decompression at the elbow were performed in patients who were previously diagnosed with leprosy neuritis. The inclusion criteria were surgical indications for ulnar nerve release and clinical treatment failure for 4 weeks in patients with cubital tunnel syndrome who had their ulnar nerve function, whether motor or sensitive, deteriorated progressively despite their receiving prednisone 1mg/kg/day and physiotherapy. For endoscopic release, the CTS Relief Kit (Linvatec. Largo, FL, USA) and a standard 4mm 30° arthroscope were used. The study included 39 patients, 29 (74.4%) males and 10 (25.6%) females. The age of the patients ranged from 12 to 64 years (33 ± 14.97). Five patients underwent bilateral release. The release demonstrated a statistically significant improvement in pain (p = 0.002), in sensitivity (p < 0.001), and in strength (p < 0.001). The best results were obtained when ulnar release was performed less than 6 months after surgery indication. None of the procedures were converted from endoscopic to open. No major complications (infection, vascular injury, and nervous injury) were reported. One patient had ulnar nerve subluxation. The endoscopic release of the ulnar nerve at the elbow in leprosy neuritis entails true and safe benefits for the patient, such as improvement in pain, sensitivity and strength.